Physico-chemical parameters of Itahari sub-metropolitan fish pond, Nepal - Thapa, Ganesh Bahadur; Pal, Joydeb (Journal of Natural History Museum, 2018)
Itahari Sub-metropolitan pond is located in the centre of the city. Influence of variations in physico-chemical parameters on aquatic flora and fauna especially in fishes brought strong stress on fishes and increases the incidence of diseases leading to high mortality. Due to lack of adequate knowledge about it, productivity of ponds is very low. In the present study, maximum and minimum variations and correlation between different physico-chemical parameters - air temperature, water temperature, pH, turbidity, total dissolved solids, dissolved carbon dioxide, ammonia, dissolved oxygen, biological oxygen demand, chloride, total alkalinity, total hardness and phosphate were taken into consideration. The water quality of fish ponds were normal except high fluctuation of chloride 4.0 - 44.87mg/l and ammonia 0.48-13.6 mg/l during manuaring period and casual addition of wastes like toilet cleaners, caustic potash etc.. Due to sudden fall in DO less than 4 mg/l during April and May, 2014 and increment of ammonia after addition of toilet wastes in Sept.19, 2015 ; mass mortality of fishes Labeo rohita, Cirrhina mrigala, Hypothalamichthys molitrix, Aristichthysnobilis occurred in the study site.